Evaluation of growth, yield and nutrient content of some Boro Rice cultivars (Research in Agriculture Livestock and Fisheries, 2015)
A field experiment was conducted at the Soil Science Field Laboratory of Bangladesh Agricultural University; Mymensingh during December 2012 to May 2013 to investigate the growth, yield and nutrient content of fifteen widely used boro rice cultivars of Bangladesh. The experiment was laid out in a Randomized Complete Block Design (RCBD) with 15 cultivars having each cultivar replicated three times. The cultivars tested in this experiment were BRRI dhan28, BRRI dhan29, BRRI dhan45, BRRI dhan47, BRRI dhan50, BR 3, BR 6, BR 14, BR 15, BR 16, BINA dhan5, IRATOM 24, Bachi boro, Chola boro and Sada boro. BR 15, BRRI dhan29 and BRRI dhan28 were the three rice cultivars having high potentials for grain and straw production during boro season. The highest yield was recorded 5.26 t/ha which is still very low compared to other rice growing countries of the world. So there is plenty of scope to increase the yield. Chola boro and Sada bore are two local land races having potentials for producing higher number of effective tillers and higher 1000 grain weight. Sada boro and Chola boro, two local cultivars were found very high in grain nitrogen content compared to other test cultivars. These two cultivars could be a nice tool for rice breeder to develop high nitrogen content rice. Chola boro, IRATOM 24 and BR 14 are three high straw-K containing varieties having breeding potentials to make our future rice plant strong. Before using these cultivars for breeding, fine tuning of the research findings is required DOI: http://dx.doi.org/10.3329/ralf.v1i1.22352 Res. Agric., Livest. Fish.1(1): 19-25, Dec 2014